The Role of Exosomes in Myeloid and Lymphoid Blood Malignancies: A Systematic Review Article - Asma Maleki; Zahra Kashani Khatib; Shaban Alizadeh; Amir Ali Hamidieh; Ali Akbar Pourfatollah (Tehran University of Medical Sciences, 2021)
Background and Aim: Blood malignancies, one of the most common cancers in the world, cause a large number of deaths each year. Many inherited and acquired factors are involved in the development of this disease. Exosomes are a very small model of cells that are secreted by most cells in the body under physiological and pathological conditions. On the other hand, they have found a special place in the treatment of these diseases because of their very small structure and biodegradability.  Materials and Methods: This study is a systematic review article. For this study, the electronic databases such as PubMed, Scopus and Web of Science were reviewed and 110 original and review articles were studied from 2000 to 2020. Exosome, blood malignancies and immunotherapy were used as keywords along with a number of other related terms such as tumor microenvironment, acute myeloid leukemia, acute lymphoid leukemia, chronic lymphoid leukemia and multiple myeloma (Exosome AND Leukemia, Leukemia AND Immunotherapy, Exosome AND Cancer, AML AND Exosome) to search in these databases. Finally, 51 sources that related to exosomes and myeloid and lymphoid blood malignancies were used. Results: The genomic profile of malignant cells and tumor microenvironment changes in the conditions of the disease. The contents of exosomes released by leukemic cells, including anti-apoptotic proteins, various microRNAs, angiogenic agents, heat shock proteins and oncogenes involved in the development of inflammatory phenotype in the target cells, are known as factors involved in the pathogenesis of leukemia. A variety of therapeutic materials such as anti-inflammatory drugs, recombinant proteins, siRNA and the inhibitor of various microRNAs can also be packaged in the exosomes with several ways and used to treat leukemia. Conclusion: Exosomes derived from malignant cells play the important role in the growth and proliferation, angiogenesis, metastasis, resistance to chemotherapeutic agent, and the escape of cancer cells from the immune system by the modification of tumor microenvironment. The role of exosomes in the creation and development of blood malignancies has been proven. Therefore, using of them will probably be very helpful and promising in the treatment of these disorders with various forms.